Predictive findings for Helicobacter pylori-uninfected, -infected and -eradicated gastric mucosa: Validation study - Watanabe, Kazuhiro (Baishideng Publishing Group Co., Limited, 2013)
AIM: To validate the usefulness of screening endoscopy findings for predicting Helicobacter pylori (H. pylori) infection status. METHODS: H. pylori infection status was determined by histology, serology, and the urea breast test in 77 consecutive patients who underwent upper endoscopy. Based on the findings, patients were categorized as H. pylori-uninfected, -infected, or -eradicated cases. Using six photos of certain sites in the stomach per case, we determined the presence or absence of the following endoscopic findings: regular arrangement of collecting venules (RAC), linear erythema, hemorrhage, fundic gland polyp (FGP), atrophic change, rugal hyperplasia, edema, spotty erythema, exudate, xanthoma, and mottled patchy erythema (MPE). The diagnostic odds ratio (DOR) and inter-observer agreement (Kappa value) for these 11 endoscopic findings used in the determination of H. pylori infection status were calculated. RESULTS: Of the 77 patients [32 men and 45 women; mean age (SD), 39.7 (13.4) years] assessed, 28 were H. pylori uninfected, 28 were infected, and 21 were eradicated. DOR values were significantly high (< 0.05) for the following H. pylori cases: uninfected cases with RAC (11.5), linear erythema (24.5), hemorrhage (4.1), and FGP (34.5); for infected cases with atrophic change (8.67), rugal hyperplasia (15.8), edema (14.2), spotty erythema (11.5), and exudate (3.52); and for eradicated cases with atrophic change (32.4) and MPE (103.0). Kappa values were excellent for FGP (0.93), good for RAC (0.63), hemorrhage (0.79), atrophic change (0.74), and MPE (0.75), moderate for linear erythema (0.51), rugal hyperplasia (0.49), edema (0.58), spotty erythema (0.47), and exudate (0.46), and poor for xanthoma (0.19). CONCLUSION: The endoscopic findings of RAC, hemorrhage, FGP, atrophic change, and MPE will be useful for predicting H. pylori infection status.